Development of Mamoji Products as Educational Media for Adolescent Women About Early Detection of Breast Cancer - Arifin, Sherina Amastasia; Jupriyono, Jupriyono; Setyaningsih, Wahyu (jitek, 2022)
Breast Self-Examination (BSE) is the development of a woman's concern for the condition of her own breasts for early detection of breast cancer. This study aims to develop MAMOJI educational media as an effort to detect breast cancer early on in adolescent girls. MAMOJI is an audio-visual-based educational media containing BSE steps. This research design uses the Research and Development method. This research was conducted up to the pilot stage using 10 samples of teenage girls at SMA Negeri 1 Gondanglegi aged 15–17 years who were already menstruating. The research instrument used a product assessment questionnaire as well as pre and post-test questionnaires to measure the knowledge of young women about BSE. After going through various processes, the results from expert validation found that MAMOJI received an assessment weight of 94.2% of material experts and 98.6% of media experts. , with a very decent category while the average results of product assessment by respondents obtained results of 94.2% (very feasible), as well as for adolescent knowledge after being analyzed and tested with paired sample t-test obtained p-value <0.001, which indicates there is a difference in knowledge before and after being given MAMOJI media. It is hoped that the development of MAMOJI can complement the existing BSE education methods, so that it is hoped that an increase in the knowledge of young women about BSE and it is hoped that BSE can be applied by young women.